1999
DOI: 10.1016/s0014-5793(99)01401-5
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐dependent interaction of the peptaibol antibiotic zervamicin II with phospholipid vesicles

Abstract: The effect of a transmembrane potential on ion channel formation by zervamicin II (ZER-II) was studied in a vesicular model system. The dissipation of diffusion potential caused by addition of ZER-II to small phosphatidylcholine vesicles was monitored using fluorescent (Safranine T) and optical (Oxonol YI) probes. Cis-positive potentials facilitated channel formation, while at cis-negative potentials, ion fluxes were inhibited. A potential-independent behavior of ZER-II was observed at high peptide concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 18 publications
(24 reference statements)
0
22
0
Order By: Relevance
“…Antiamoebin I has the amino acid sequence: Ac-Phe 1 -Aib-Aib-Aib-Iva-Gly-Leu-Aib 8 -Aib-Hyp-Gln-Iva-Hyp-Aib-ProPhl 16 . By using the uniformly 13 C, 15 N-labeled sample of Aam-I, the set of conformationally dependent J couplings and 3h J NC couplings through H-bonds were measured. Analysis of these data along with the data on magnetic nonequivalence of the 13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antiamoebin I has the amino acid sequence: Ac-Phe 1 -Aib-Aib-Aib-Iva-Gly-Leu-Aib 8 -Aib-Hyp-Gln-Iva-Hyp-Aib-ProPhl 16 . By using the uniformly 13 C, 15 N-labeled sample of Aam-I, the set of conformationally dependent J couplings and 3h J NC couplings through H-bonds were measured. Analysis of these data along with the data on magnetic nonequivalence of the 13 …”
mentioning
confidence: 99%
“…In model membrane systems, Zrv-IIB forms strongly voltage-dependent ionic channels with a characteristic set of dozen conductance levels [14] [15], while Aam-I in analogous systems displays voltage-independent leakage and weak voltage-dependent conductance on its top [16 -18]. Comparison of the peptaibol antimalarial activities indicated that antiamoebins are on average, by one order of magnitude less active than zervamicins, and display an IC 50 value of 5 mm [9].…”
mentioning
confidence: 99%
“…The property of Zrv-TEMPO-16 to form ion channels was tested by means of the method that has been described before. 3 The analog shows the same activity as the native compound. …”
Section: Antibacterial Assaymentioning
confidence: 96%
“…The product was shown to be pure (96%) by RP16 HPLC analysis. The chromatography has been carried out at a flow rate of 1 mL/min and by isocratic elution with 55% CH 3 OH/45% 0.01M NH 4 OAc for 5 min, followed by a gradient elution from 0 to 80% CH 3 OH/CH 3 Condensation of [des-Phl 16 ]-Zrv IIA with 4-amino-TEMPO (Sigma, USA) was performed by the racemizationfree HATU method in NMP and the product, Zrv-TEMPO-16, was isolated by the method described above. After gel filtration the peptide was purified by preparative reversed phase high performance liquid chromatography (RP-HPLC) using the column Diasorb-130-C16T (4 ϫ 250 mm) purchased from BioChimMak (Russia).…”
Section: Synthesis and Characterization Of The Spin-labeled Zrv-iiamentioning
confidence: 99%
See 1 more Smart Citation